Chronic disease management interventions for people with chronic kidney disease in primary care: a systematic review and meta-analysis. Issue 1 (23rd January 2017) - Galbraith, Lauren; Jacobs, Casey; Hemmelgarn, Brenda R; Donald, Maoliosa; Manns, Braden J; Jun, Min
Abstract: Background: Primary care providers manage the majority of patients with chronic kidney disease (CKD), although the most effective chronic disease management (CDM) strategies for these patients are unknown. We assessed the efficacy of CDM interventions used by primary care providers managing patients with CKD. Methods: The Medline, Embase and Cochrane Central databases were systematically searched (inception to November 2014) for randomized controlled trials (RCTs) assessing education-based and computer-assisted CDM interventions targeting primary care providers managing patients with CKD in the community. The efficacy of CDM interventions was assessed using quality indicators [use of angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB), proteinuria measurement and achievement of blood pressure (BP) targets] and clinical outcomes (change in BP and glomerular filtration rate). Two independent reviewers evaluated studies for inclusion, quality and extracted data. Random effects models were used to estimate pooled odds ratios (ORs) and weighted mean differences for outcomes of interest. Results: Five studies (188 clinics; 494 physicians; 42 852 patients with CKD) were included. Two studies compared computer-assisted intervention strategies with usual care, two studies compared education-based intervention strategies with computer-assisted intervention strategies and one study compared both these intervention strategies with usual care. Compared with usual care, computer-assisted CDM interventions did not increase the likelihood of ACEI/ARB use among patients with CKD pooled OR 1.00 [95% confidence interval (CI) 0.83–1.21]; I 2 = 0.0%. Similarly, education-related CDM interventions did not increase the likelihood of ACEI/ARB use compared with computer-assisted CDM interventions [pooled OR 1.12 (95% CI 0.77–1.64); I 2 = 0.0%]. Inconsistencies in reporting methods limited further pooling of data. Conclusions: To date, there have been very few randomized trials testing CDM interventions targeting primary care providers with the goal of improving care of people with CKD. Those conducted to date have shown minimal impact, suggesting that other strategies, or multifaceted interventions, may be required to enhance care for patients with CKD in the community.